(untitled) (International journal of artificial intelligence, 2025)
This article explores effective strategies for managing cultural diversity in TESOL (Teaching English to Speakers of Other Languages) classrooms. It emphasizes the importance of recognizing cultural differences, promoting inclusivity, and creating an environment where all learners feel valued. The article discusses various methods, including culturally responsive teaching, inclusive curriculum design, classroom activities promoting intercultural communication, and fostering an open, respectful learning environment. Additionally, it addresses the challenges and potential drawbacks of these strategies, offering practical advice for teachers to navigate cultural complexities while ensuring effective language acquisition for all students.